2008
DOI: 10.1001/archinte.168.18.2009
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Hepatitis C Screening Tool in Primary Care

Abstract: Background: Although hepatitis C virus (HCV) has an estimated national prevalence of 1.8%, testing rates are lower than those recommended by guidelines, particularly in primary care. A critical step is the ability to identify patients at increased risk who should be screened. We sought to prospectively derive and validate a clinical predication tool to assist primary care providers in identifying patients who should be tested for HCV antibodies. Methods: A total of 1000 randomly selected patients attending an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Furthermore, the use of a proportionally allocated population based sample asserts that the derived results feature the Egyptian population. The study conducted by McGinn et al, in USA was limited by surveying population coming from an inner-city primary care practice, thus the results do not represent the true community [21]. Other studies validated their tool on hospital based small samples [19, 22] or on certain risk groups [5, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of a proportionally allocated population based sample asserts that the derived results feature the Egyptian population. The study conducted by McGinn et al, in USA was limited by surveying population coming from an inner-city primary care practice, thus the results do not represent the true community [21]. Other studies validated their tool on hospital based small samples [19, 22] or on certain risk groups [5, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, infection with hepatitis C virus (HCV) is common among people who inject drugs (PWID) 1. Estimates suggest that >70% of new cases of HCV infection are associated with injecting drug use 2 3.…”
Section: Introductionmentioning
confidence: 99%
“…133 One blood donor study associated HCV with older mean age 130 while the other did not. 131 In general population studies, HCV was associated with increased mean age 141 and decade of birth (with people born from 1940 to 1959 having the highest prevalence), 132 but not age ,50 years 120 or age ,60 years. 123 c. Race/ethnicity and national origin.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…132,141 Among blood donors, one study found that Hispanic ethnicity led to a higher risk of HCV than white race in a multivariate analysis, 140 but another study did not come to this conclusion. 133 Being Asian vs. white was associated with having a lower prevalence of HCV among blood donors in a multivariate analysis.…”
mentioning
confidence: 99%